Carbohydrate chemistry : state of the art and challenges for drug development : an overview on structure, biological roles, synthetic methods, and application as therapeutics - Cipolla, Laura, 1968- (London : Imperial College Press, 2016)
"The structural complexity and the synthetic challenges facing glycans have historically hampered efforts to study their multifaceted roles and the application of carbohydrates in drug development. However, in very recent years, new synthetic techniques flanked by the growing knowledge about carbohydrate involvement in physiological and pathological states has spurred renewed interest in the chemistry, biology and therapeutic potentialities of carbohydrates. This book offers an overview of key aspects of carbohydrate biology and chemistry that are fundamental for the design of novel therapeutics. The four-part structure of this book introduces these essential components to life, starting from their structure and biological roles and covering analytical methods and synthesis which pave the way for the development of a wide range of therapeutic applications. Leading experts from around the world are brought together to offer their recent research with the ultimate aim of enlightening the reader on the complex yet exciting field of carbohydrate chemistry. Academic and industrial researchers in structural biology, drug discovery and carbohydrate chemistry will find this book an essential guide to the latest research and future potential of medicinal chemistry."--
Mode of access: World Wide Web.
Title from PDF file title page (viewed September 14, 2015).
Electronic reproduction.
Includes bibliographical references and index.
Keywords: Carbohydrates -- Synthesis; Pharmaceutical chemistry; Drug development; Electronic books